ANALISIS HUBUNGAN ANTARA KEAMANAN DAN PEMAHAMAN PENGGUNA QRIS DENGAN EFEKTIVITAS TRANSAKSI DIGITAL MAHASISWA KOTA BANDUNG MELALUI REGRESI LINIER BERGANDA - Siregar, Nur Mardhatillah; Wisna, Nelsi; Asniar, Asniar (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the relationship between the security and user understanding of QRIS and the effectiveness of digital transactions among students. Additionally, this research seeks to explore the extent to which understanding QRIS security contributes to the effective use of this technology by students. This research employs a survey method with a quantitative approach and a cross-sectional research design. Data were collected through surveys distributed to students in Bandung using purposive sampling techniques. Multiple linear regression analysis was used to test the relationship between the security and user understanding of QRIS and the effectiveness of digital transactions. The analysis results indicate that user understanding of QRIS has a significant impact on the effectiveness of digital transactions. Conversely, the security factor does not show a significant influence. The study concludes that user understanding of QRIS is a key factor in enhancing the effectiveness of its use, whereas user security does not have a significant impact. Therefore, it is recommended to improve user education related to QRIS understanding to enhance the effectiveness of digital transactions.